A point mutation in Fgf9 impedes joint interzone formation leading to multiple synostoses syndrome. (7th February 2017) - Tang, Lingyun; Wu, Xiaolin; Zhang, Hongxin; Lu, Shunyuan; Wu, Min; Shen, Chunling; Chen, Xuejiao; Wang, Yicheng; Wang, Weigang; Shen, Yan; Gu, Mingmin; Ding, Xiaoyi; et al.
Abstract: Human multiple synostoses syndrome (SYNS) is an autosomal dominant disorder characterized by multiple joint fusions. We previously identified a point mutation (S99N) in FGF9 that causes human SYNS3. However, the physiological function of FGF9 during joint development and comprehensive molecular portraits of SYNS3 remain elusive. Here, we report that mice harboring the S99N mutation in Fgf9 develop the curly tail phenotype and partially or fully fused caudal vertebrae and limb joints, which mimic the major phenotypes of SYNS3 patients. Further study reveals that the S99N mutation in Fgf9 disrupts joint interzone formation by affecting the chondrogenic differentiation of mesenchymal cells at the early stage of joint development. Consistently, the limb bud micromass culture (LBMMC) assay shows that Fgf9 inhibits mesenchymal cell differentiation into chondrocytes by downregulating the expression of Sox6 and Sox9 . However, the mutant protein does not exhibit the same inhibitory effect. We also show that Fgf9 is required for normal expression of Gdf5 in the prospective elbow and knee joints through its activation of Gdf5 promoter activity. Signal transduction assays indicate that the S99N mutation diminishes FGF signaling in developmental limb joints. Finally, we demonstrate that the conformational change in FGF9 resulting from the S99N mutation disrupts FGF9/FGFR/heparin interaction, which impedes FGF signaling in developmental joints. Taken together, we conclude that the S99N mutation in Fgf9 causes SYNS3 via the disturbance of joint interzone formation. These results further implicate the crucial role of Fgf9 during embryonic joint development.